A novel green composite conductive material enhancing anaerobic digestion of waste activated sludge via improving electron transfer and metabolic activity. (15th July 2022) - Liu, Haoyu; Xu, Ying; Li, Lei; Yuan, Shijie; Geng, Hui; Tang, Yanfei; Dai, Xiaohu
Highlights: A novel green magnetic straw-based biochar (MSBC) was prepared. MSBC enhanced volatile fatty acid and methane production from sludge. MSBC promoted the intra- and extracellular electron transfer efficiency. MSBC improved acetoclastic methanogenesis and direct interspecies electron transfer. Abstract: Anaerobic digestion (AD) of waste activated sludge (WAS) is usually limited by the low generation efficiency of methane. The addition of composite conductive materials (CMs) is a promising strategy to enhance AD performance. In this study, a new green magnetic-straw-based biochar (MSBC) was synthesised by a simple ball-milling/carbonisation method, and its effects on AD performance of sludge were investigated. Experimental results showed that the as-synthesised MSBC had an intrinsic graphene-oxide-like structure, with Fe species serving as electroactive sites; these characteristics translate into a high electron transfer (ET) capability. After adding MSBC, the volatile fatty acid production and methane yield were significantly increased by 14.13% and 45.36%, respectively. Analysis of the changes in the ET system activities, hydrogenase activities, Cyt-C concentrations and the electron transfer capacity of the sludge sample with and without the MSBC revealed that the MSBC enhanced intracellular ET and changed the extracellular ET pathway from indirect interspecies hydrogen transfer to direct interspecies electron transfer (DIET), which would be responsible for increasing methane production and proportion in the biogas. However, further analyses of key enzyme activities and the microbial community indicated that the MSBC reinforces the methanogenesis pathway by creating a favourable environment (i.e., by enhancing hydrolysis-acidification and DIET-based CO2 reduction) for acetoclastic methanogens. These findings, however, are expected to provide an important reference for developing CMs application in AD. Graphical abstract: Image, graphical abstract